Dry bean progenies evaluation and estimates of genetic parameters in the "alto São Francisco" region of the state of Minas Gerais - Pereira Filho, Israel Alexandre; Ramalho, Magno Antônio Patto; Ferreira, Sérgio (Pesquisa Agropecuaria Brasileira, 2014)
Fifty dry bean (Phaseolus vulgaris L.) progenies were evaluated at Fazenda Experimental Sertãozinho of EPAMIG at Patos de Minas, MG, Brazil, during the growing seasons of 1983/84 and 1984/85, as for progenies x year interaction, performance, genetic and phenotypic parameters for number of pods per plant, number of seed per pod, 100 seed weight, and grain production. No significant interaction between progenies x year were detected for all traits. Some progenies out yielded the cultivar 'Carioca' used as check and hence showed the agronomic potencial of the progenies. Heritability estimates for the primary yield components were higher than heritability for grain yield but all estimates seemed to indicate possibility of progress with selection. Genetic and phenotypic correlation between number of pods per plant and number of seeds per pod were positive and significant. Correlations between these two traits and grain yield were also positive, indicating that number of pods per plant and number of seeds per pod should be considered in a selection program.